THE IMPLEMENTATION OF REVITALIZATION POLICY IN VOCATIONAL HIGHER EDUCATION PROGRAM/IMPLEMENTASI KEBIJAKAN REVITALISASI PENDIDIKAN TINGGI VOKASI PROGRAM DIPLOMA III - Rani Intan (Sekolah Vokasi Universitas Diponegoro, 2022)
Revitalization of Vocational Higher Education aims to create higher education graduates who have the competence, qualifications, and skills that link and match with the needs of the industrial world and the world of work/business (DUDI). The purpose of the study was to analyze the efforts to optimize the management of study programs through the revitalization of vocational education with the object of research being the Diploma III Administrative Management, Mechanical Engineering, Civil Engineering and Computer Engineering at the Islamic University